(untitled) (KULT_online, 2009)
Ewa Mayer’s study Théâtre de la proximité concentrates on an oft neglected period in French and, consequently, European theatre, namely the transition between classicism and Enlightenment in the late 17th and the early 18th century. At that time dramatists such as Voltaire, Crébillon (père) and Houdar de La Motte tried to establish reformatory ideas in their poetological as well as dramatic writings which Mayer collectively calls ’Théâtre de la proximité’. Certain dramatists developed this aesthetics of proximity to surmount the classicist ideals of objectivity and universality and bring the subjectivity of both the dramatis personae and the spectators to the forefront – the aim being an (ideally) complete, generally emotional identification between stage players and audience members.